Physicians' perspective on the clinical meaningfulness of inflammatory bowel disease trial results: an International Organization for the Study of Inflammatory Bowel Disease (IOIBD) survey. Issue 6 (19th January 2018) - Olivera, P.; Sandborn, W. J.; Panés, J.; Baumann, C.; D'Haens, G.; Vermeire, S.; Danese, S.; Peyrin‐Biroulet, L.
Summary: Background: Several novel compounds are being developed for inflammatory bowel diseases (IBD). In addition, biosimilar drugs are being approved. An increasing number of head‐to‐head, superiority and non‐inferiority trials in patients with IBD are expected in the future. The clinical relevance of the magnitude of the effect size is often debated. Aim: To better understand physicians' perspectives on the clinical meaningfulness of IBD trial results. Methods: We conducted an online survey among all IOIBD (International Organization for the Study of Inflammatory Bowel Diseases) members, asking their opinion on the clinical relevance of the results of IBD trials. Results: Forty‐six IOIBD members responded to the survey (52.3%). In biologic‐naïve ulcerative colitis (UC) and Crohn's disease (CD) patients, most of the participants considered a 15% difference with placebo for clinical remission and endoscopic remission to be clinically relevant. In head‐to‐head trials, most of participants considerer a 10% difference between groups for clinical remission and endoscopic remission to be clinically relevant. Half of respondents considered 10% to be an adequate margin in non‐inferiority trials. In bioequivalence studies, most of the participants considered adequate a ± 5% difference between a biosimilar and the originator for pharmacokinetic parameters, efficacy, safety and immunogenicity. Regarding safety, the difference between two drugs considered clinically relevant varied from 1% to 5%, depending on the type of adverse event. Conclusions: This is the first survey exploring how physicians perceive IBD trial results, providing an estimation of the magnitude of the difference between treatment arms that may directly influence clinical practice. Abstract : Linked Content This article is linked to Sparrow paper. To view these article visit https://doi.org/10.1111/apt.14574 .